Mask Wearing Practice- First Line Defence against Communicable Diseases - Ahmad, Mushtaq; Pasha, A K M Mustafa Kamal (Journal of Armed Forces Medical College, Bangladesh, 2024)
Abstract not available JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 1-2